Study of Individual and Organizational Outcomes of Career Anchors in General Education Office of Tehran - میثم دهناد; یوسف محمدی مقدم; علی دلاور; زهرا علیپور درویشی (مطالعات منابع انسانی, 2019)
Background and Objective: Career anchors have been considered a human resources development strategy. Human resources managers have realized that it is necessary to plan and organize career paths and the progress trend in order to retain human resources and achieve appropriate outcomes for organizations. This study aims to analyze the effects of career anchors on individual outcomes including individual maturity and human resources sustainability as well as organizational outcomes including organizational civilization and organizational hopefulness. Methodology: This is an applied descriptive study, in which the statistical population consisted of 900 employees working at the general education office of Tehran. The stratified random sampling method was employed to select 270 individuals as the research sample. A researcher-made questionnaire was used as a data collection tool, the validity of which was confirmed through content and face validity tests, whereas its reliability was confirmed through Cronbach’s alpha. The structural equation modeling (SEM) (path analysis) was used for data analysis and hypothesis testing. Findings: Career anchors had positive, significant effects on individual outputs. They also affected some of the organizational outputs. Accordingly, it was not confirmed that technical and functional competencies, work independence, and pure challenge affected organizational civilization. Furthermore, the effect of work independence on organizational hopefulness was not confirmed. Conclusion: Identifying career models for key individuals to plan their career paths can both help their individual development and improve organizational productivity.